Genetics, diagnosis and clinical features of congenital hypodysfibrinogenemia: a systematic literature review and report of a novel mutation. (6th March 2017) - Casini, A.; Brungs, T.; Lavenu‐Bombled, C.; Vilar, R.; Neerman‐Arbez, M.; de Moerloose, P.
Abstract : Essentials Hypodysfibrinogenemia is rarely reported among the congenital fibrinogen disorders. This first systematic literature review led to identification of 51 hypodysfibrinogenemic cases. Diagnosis based only on functional/antigenic fibrinogen ratio may be insufficient. Family studies show an incomplete segregation of mutation with the clinical phenotypes. Summary: Background: Hypodysfibrinogenemia is a rare disease characterized by decreased levels of a dysfunctional fibrinogen. It shares features with both hypo‐ and dysfibrinogenemia, although with specific molecular patterns and clinical phenotypes. Objectives: To better define the genetics, the diagnosis and the clinical features of hypodysfibrinogenemia. Patients/Methods: A systematic literature search led to 167 records. After removal of duplicates, abstract screening and full‐text reviewing, 56 molecular and/or clinical studies were analyzed, including a novel FGB missense mutation in a woman with a mild bleeding phenotype. Results: A total of 32 single causative mutations were reported, mainly in the COOH‐terminal region of the γ or Aα chains at heterozygous or homozygous state. Seven additional hypodysfibrinogenemias were due to compound heterozygosity. The hypofibrinogenemic phenotypes were a result of an impaired assembly or secretion or an increased clearance of the fibrinogen variant, whereas the dysfibrinogenemic phenotype was mainly a result of a defective fibrin polymerization and an abnormal calcium or tPA binding. Among 51 identified index cases, a functional/antigenic fibrinogen ratio < 0.7 had a sensitivity of 86% for the diagnosis of hypodysfibrinogenemia. Eleven patients (22%) were asymptomatic at time of diagnosis, 23 (45%) had a mild bleeding phenotype with mainly obstetrical or gynecologic‐related hemorrhage and 22 (43%) had experienced at least one thrombotic event, including 23 venous and eight arterial thromboses. Conclusions: This first systematic review on hypodysfibrinogenemia shows the heterogeneity of causative mutations and that misdiagnosis could occur in relation to the functional and antigenic fibrinogen levels. Family studies reveal an incomplete segregation of the mutation with the clinical phenotype.